Shaftesbury as Popperian: critical rationalism before its time? Part I - Lydia Amir (Analiza i Egzystencja, 2016)
Shaftesbury has assigned humor an unparalleled role within philosophy, which maybe encapsulated in the following tenets: (1) ridicule is the test of truth; (2) humor andgood humor have a habilitating function with regard to truth; (3) the most effectivecriticism is humorous; and (4) humor is the mark of rationality. In the present article,I introduce Shaftesbury’s views on ridicule, good humor and humor in order to assessboth the originality and viability of Shaftesbury’s contribution. I argue, first, thatShaftesbury’s views on ridicule as a test of truth and on good-humor as habilitatingtruth are thoroughly original, but cannot be implemented without adhering to hismetaphysics and epistemology. Second, Shaftesbury’s views on humor are only partiallyoriginal, though these can be implemented independently of metaphysical andepistemological assumptions for the greatest benefit of philosophers in general andcritical rationalists in particular. I conclude that not only does Shaftesbury anticipatethe view that critical thinking is the core of rationality, the main principle of the viewknown as critical rationalism associated with the renown 20th century philosopherof science and social philosopher, Karl Popper, but he also offers a viable meansto enhance criticism as rationality by taking into consideration the psychologicalresistance to criticism that Popper acknowledges but refuses to address.